ETNOSEMANTIK DALAM KLASIFIKASI KAIN TENUN MASYARAKAT BIMA - Fitriani, Dini Eka; Mahsun, Mahsun; Saharudin, Saharudin (The Center for Language Development, Mataram State Islamic University., 2024)
Indicates that it is closely related to the perspective, social status, traditions and customs of the local community. Therefore, it is interesting to research in more depth from the linguistic and cultural aspects. The aim of this research is to describe the lexemes used to label woven fabrics in the Bima community and explain the cultural views of the local community which are reflected in the lexemes for woven fabrics in the Bima community. The research method used is descriptive qualitative with data collection using interviews, documentation and observation. The results of the research show that there are five types of woven fabric based on the yarn used, namely tembe nggoli kabali, tembe galendo, tembe salungka, tembe mesrais, and tembe kafa na'e, while there are 15 types of woven fabric based on motifs, including tembe salungka nggusu waru, tembe salungka karai cepe, tembe salungka kabate oi moti, tembe salungka ante fare, tembe salungka fu'u ringi dan pariah, tembe salungka kakando, tembe salungka dumu kakando, tembe salungka coma kapi, tembe salungka mada sahe, tembe salungka kapempe, tembe salungka raba, tembe salungka nasi, tembe salungka uma lengge, tembe salungka bunga satako, and tembe salungka kapi keu. In the color category of Bima woven cloth there are nine colors, namely yellow, green, blue, black, white, red, brown, purple and orange. For the community, lace weaving is an activity that must be carried out by every woman in this village, of all ages, regardless of their status and educational background.